How a Chinese social media platform recontextualises Russian strategic narratives: A case study in news translation - Rui Wang (JoSTrans: The Journal of Specialised Translation)
The free circulation of online videos across platforms, languages and cultures due to their low-cost and easy-to-produce characteristics allows participatory media agents (Jenkins 2004) to reuse and repurpose ready videos for their own political and commercial aims. This paper explores this understudied phenomenon through a case study of news videos which were originally produced by a Russian international broadcaster for YouTube but were later recontextualised by a Chinese state-aligned media agent, The Observer, for Bilibili. Using a contrastive analysis, this paper examines the translation strategies that the video uploader adopted in its appropriation of the source videos for Bilibili users. This paper also examines how the uploader’s edits, like the selection of videos, contribute to changes to the Russian strategic narratives (Miskimmon et al. 2013, 2017) in the target context. The data analysis demonstrates that by adopting suitable editing techniques the Chinese media agent has significantly changed the Russian strategic narratives to serve its own political and market agendas. As part of its translation process for the target media context, the uploader has taken various factors into account, such as the Bilibili audiences’ consumption habits, their entertainment needs, their pre-existing stereotypes of Putin, Russia and China, and its own propaganda missions.